What is there to buy? : an analysis of the food environment in public and private schools in the Federal District - Araújo, Giovanna Soutinho (2025)
This descriptive ecological study evaluated the food environment of 18 public and private schools in the Federal District (DF), Brazil, by analyzing food availability within schools and in their surroundings (250 m, 400 m, and 800 m buffers). Food retail outlets (FROs) were georeferenced and classified according to the NOVA food classification. School principals were interviewed to assess the in-school food environment. Analyses considered the Social Vulnerability Index (SVI; low or medium/high) and school type. Among 911 FROs identified, 40.2% predominantly sold ultra-processed products. Most schools (83.3% within a 250 m radius) had at least one nearby FRO. Private schools—mostly in low-SVI areas—had higher densities of surrounding FROs at all buffer distances, with significance for total density at 400 m (p = 0.03) and for unhealthy outlets at 800 m (p < 0.01). Low-SVI areas had higher densities of both healthy (p = 0.01) and unhealthy (p < 0.01) outlets, with differences across multiple buffers. In canteens, sugar-sweetened beverages were the most common ultra-processed items (75%). The median ratio of ultra-processed to minimally processed food subgroups was 2.7 (0.5–6.0), and all private schools with a canteen sold at least one item prohibited by current regulations. Overall, the DF school food environment was characterized by a predominance of unhealthy foods, with disparities by school type and social vulnerability.